Peran Bank Syari'ah dalam Pengembangan Dunia Usaha - Author: Muhammad (Universitas Islam Indonesia, 2006)
The Shari'ah banking system applies the profit and lose sharing system. This system criticize the weakness of the conventional bank system that covers transaction, bank commitment to save money, the rigidity of transaction, real sector position, and capital retum. Departing from those weakness, the shari'ah banking has to play an important role because it rejects interest system or bankung without interest, to bridge economy activities fairly, the shari'ah banking is free from negative spread, and it keeps the balancing between real sector and monetary sector.